Paris Hollywood. (Paris : Galerie 1900-2000, 1981)
Prou, Rene ; Bel Geddes, Norman ; Dorwin Teague, Walter ; Weber, Kem ; Deskey, Donald ; Rohde, Gilbert ; Gray, Eileen ; Rateau, Armand Albert ; Jallot, Leon ; Mallet-Stevens, Robert ; Lacroix, Boris Jean ; etc.
Paris Hollywood, Galerie 1900-2000, Paris, decembre 1981 - janvier 1982
boek
Keywords: Amerika